Assessment of Uneven Wear of Freight Wagon Brake Pads - Sergii Panchenko; Juraj Gerlici; Alyona Lovska; Vasyl Ravlyuk (Applied Sciences)
This study deals with the problem of uneven wear of brake pads of wagons caused by a set of structural, dynamic, technological and operational factors. It has been found that an uneven distribution of the brake pad pressure force leads to higher maintenance costs and lower braking efficiency. The main causes of uneven wear are worn kinetostatic units, differences in the geometric parameters of pads, and imperfections in the lever transmission design. A method for optimizing the distribution of the pressure force using weight coefficients and the Lagrange function has been developed; it reduces the uneven wear of brake pads to 8–10% compared to that of a typical wagon bogie brake system, which is 20–35%. The experiments conducted have shown that for a mileage of 74,400 km and with the air distributor in empty mode, the wear of the pads is 19.6–28 mm, while in the loaded mode it amounts to 27.53–38.04 mm. The stress state of brake pads was determined with consideration of the weight coefficients. It was found that for abnormal wear of brake pads, their strength is not observed. The strength of the wheel when interacting with an abnormally worn pad has also been assessed. The resulting stresses are 1.5% higher than those that occur when the wheel interacts with the pad with nominal dimensions. The results of the research will contribute to the database of developments to be used for designing of modern structures of tribotechnical pairs of rolling stock and increasing the efficiency of railway transport.